Americanizing Canadian Nursing: Nursing Regulation Drift - Kathleen MacMillan; Judith Oulton; Rachel Bard; Wendy Nicklin (McMaster University Library Press, 2017)
Recent regulatory changes mean Canadian nurses are writing a US-based entry to practice exam and a US company is assessing credentials of internationally educated nurses (IENs) for Canadian registration. This paper asserts that this policy direction has significant consequences for Canadian content and integrity of education programs, francophone parity in testing, and the future of primary health care and health system reform. Furthermore, writing a US exam means Canada is at risk of losing nursing human resources to the United States while trade agreements endanger Canadian nursing intellectual property.